The Power of Technology for Learning - Barsky, N.P. (Springer, 2017)
In today’s dynamic global business environment where knowledge is a main asset and learning becomes the most important process, Business Education needs to employ the right practices to develop future leaders. Businesses require graduates that become true experts. But can business schools indeed create learning experiences that address the needs of the global marketplace? Can they teach students to build learning organizations?